Family Support Related to Quality of Life on Schizophrenia Patients - Jek Amidos Pardede; Jenny Marlindawani Purba (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Schizophrenia is a disease or mental disorder experienced by most people in the world. The family support shown through attitudes, actions, and acceptance will have a profound effect on the quality of life of schizophrenia patients. This study aims to find out the relationship between family support and quality of life in schizophrenia patients. This research method uses a descriptive correlation with a cross-sectional approach. The population in this study was all 1,134 schizophrenic patients in Medan Psychiatric Hospital with a sample of 92 people with purposive sampling techniques. The data collection tool uses questionnaires that have been tested for validity and reliability. To measure family support by providing questionnaires as many as 11 statements and to measure the quality of life of schizophrenic patients by quizzing as many as 16 statistical test statements using chi-square trials. The results of this study were analyzed univariately obtained the support of the majority of families (65.2%) and the quality of life of schizophrenia patients is majority low (57.6%) with a p-value <0.007. in conclusion, there is a significant relationship between family support and quality of life. schizophrenic patients.